EFFICACY OF OZONIZED SEA BUCKTHORN OIL IN THE TREATMENT OF PERIODONTAL DISEASES IN TOBACCO-DEPENDENT PATIENTS - V.M. Zubachyk; M.P. Ilchyshyn (Український стоматологічний альманах, 2018)
Tobacco smoking remains one of the most important problems of the present time due to significant prevalence and harmful effects on human health. The area of primary contact with components of tobacco smoke is organs and tissues of the oral cavity, oral fluid. In this regard, there is a theoretical and practical interest in the problem of studying the nature and mechanisms of the damaging effects of tobacco smoke during smoking, in particular, on periodontal tissues. Depending on the duration and intensity of smoking misuse, one of the modern methods of treatment is oxygen-ozonized therapy (ozonotherapy), which reduces the risk of polypragrammia and is well combined with both medicines and phytopreparations.